Dampak Tinggi Gelombang Signifikan Terhadap Kekeruhan Di Selat Bengkalis - Theo Hasido Silalahi; Sigit Sutikno; Koichi Yamamoto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Bengkalis island is the main island of Bengkalis Regency, Riau Province, where the district capital is located and is the border of Indonesia and Malaysia. Bengkalis island often experiences a reduction in shoreline (abrasion) which can reach 38.02 meter/year and an additional shoreline (sedimentation) which can reach 29.77 meter/year. The process of abrasion and sedimentation occurs as a result of a series of waves that rub against the shore and transport sediment. Sediment transport can take the form of suspended loads, this is what causes the Bengkalis strait to become turbid, turbidity can be bad for the ecosystem and construction around the strait. Is is the necessary to study the effect of significant wave height and turbidity around the Bengkalis strait. This study use Turbiditymeter to collect turbidity data, the equipment will be assembled and placed on the bottom of the straitfor 2 month. The result of this study indicate that significant wave height has a effect on the turbidity at the study site.Keywords: significant wave height, turbidity, turbiditymeter